Income tax application into the accounting of sports clubs in the Czech republic - Radmila Herzánová (Palacký University Olomouc, 2010)
Sports clubs are non-profit organizations the mission of which is mainly concerned with sports activities, but often supplemented by other activities such as provision of sports and educational trainings or of social events promoting healthy life style. To gain income, sports clubs often do business in the fields somehow related to sports, as is tourism, outdoor management training, provision of assessment centres, etc. All activities of such organisations have to be accounted in the right way according to their nature in order to satisfy the Income Tax regulations. Non-profit organisations lack quality and up-to-date expert literature on this topic which would help them to reveal frequent mistakes in their accounting and tax reporting. Moreover, the management of sports clubs often underestimates the importance of precise accounting and tax management. Nowadays the accounting of non-profit sports organisations has been gaining more interest by tax administrators and sports clubs may have to reassess some of their accounting procedures. This article deals with ambiguous statements in the Act on Income Tax and with difficult employment of such regulations into the accounting of sports clubs.